Coupling Effects of Yaw Damper and Wheel-Rail Contact on Ride Quality of Railway Vehicle - Hai Zhang; Xiangrui Ran; Xiugang Wang; Fengtao Lin; Qi Jiang (Shock and Vibration)
The ride quality of the railway vehicle is not only affected by the wheel-rail contact geometry but also by the yaw damper. In order to explore this variation law, an equivalent parameter model of the yaw damper was established based on the internal characteristics of the yaw damper, which is both accurate and efficient. Then, considering the influence of wheel wear and wheel-rail contact geometry, ride quality of the railway vehicle under different parameters of yaw damper and wheel-rail contact parameters was analysed. The results show that the wheel-rail contact points are scattered on the wheel profile after the wheel wears out, and the equivalent conicity also tends to increase with the increasing operating mileage. The distribution of ride quality space is sensitive to the change of equivalent conicity. In the low equivalent conicity area, the expansion rate of excellent ride quality space is faster. In the high equivalent conicity area, the expansion rate of qualified ride quality space is faster. Appropriate additional stiffness which is oil stiffness in parallel with structural damping in the equivalent parameter model of the yaw damper can improve the vehicle ride quality. The lateral ride quality is influenced obviously with the condition of the damping of the yaw damper being less than 440 kN·s·m−1. Properly reducing the joint stiffness of the yaw damper could reduce the influence of characteristic parameters of the yaw damper and equivalent conicity of the wheel-rail contact on vehicle lateral ride quality. The optimized characteristic parameters of the yaw damper are used in the actual vehicle test, and the ride quality is effectively improved.